2007 IEEE/LEOS International Conference on Optical MEMS and Nanophotonics 2007
DOI: 10.1109/omems.2007.4373837
|View full text |Cite
|
Sign up to set email alerts
|

Novel Large Area Applications Using Optical MEMS

Abstract: We focus on the potential of Optical MEMS for large area applications and discuss why it is very beneficial to use micro system technologies, especially Optical MEMS, on large scale. We present micromirror applications for daylight guiding into buildings and for light concentration in solar technologies as well as the corresponding technological approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…We proposed the methodology in 2003 [14][15][16][17] and research work has been published subsequently. [18][19][20] Figure 1 illustrates a MEMS-based active window in a room providing a smart personal environment beneficial for users. For intuitive reasons, the micromirrors are shown by unrealistically large black bars in the window for clear identification.…”
Section: Different Concepts For Smart Windows: Reviewing Today's Stat...mentioning
confidence: 99%
See 1 more Smart Citation
“…We proposed the methodology in 2003 [14][15][16][17] and research work has been published subsequently. [18][19][20] Figure 1 illustrates a MEMS-based active window in a room providing a smart personal environment beneficial for users. For intuitive reasons, the micromirrors are shown by unrealistically large black bars in the window for clear identification.…”
Section: Different Concepts For Smart Windows: Reviewing Today's Stat...mentioning
confidence: 99%
“…[22][23][24]50) This review paper is based on a recent conference paper (MOC) and also contains material that has already been published. 16,[18][19][20][21][50][51][52][53] However, the content of Sects. 4-6 including all figures in these sections are based on new data.…”
Section: Functionality Of Dynamic Windows Based On Mems Micromirror A...mentioning
confidence: 99%
“…Today they are already applied in many cases: For example as barcode scanner [4], or in projectors [5]. We have already shown that the possibility to create micromirror arrays in principle [6]. Today we want to present our latest results.…”
Section: Introductionmentioning
confidence: 99%
“…Light steering micromirrors have been developed at INA (Institute of Nanotechnologies und Analytics), University of Kassel [9], [10], [11].…”
Section: Introductionmentioning
confidence: 99%